2015
DOI: 10.1111/boj.12322
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ‘islands’ in the landscape: low gene flow, effective population size and genetic divergence in the shrubHakea oldfieldii(Proteaceae)

Abstract: The genetic structure of disjunct populations is determined by founding genetic properties, demographic processes, gene flow, drift and local selection. We aim to identify the genetic consequences of natural population disjunction at regional and local scales in Hakea oldfieldii using nuclear and plastid markers to investigate long‐term effective population sizes and gene flow, and patterns of diversity and divergence, among populations. Regional divergence was significant as shown by a consistent pattern in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
(98 reference statements)
2
11
0
1
Order By: Relevance
“…Little is known of the mating system of H. oldfieldii. In the study of Sampson et al (2015), inbreeding coefficients were positive (F = 0.036-0.198) but did not indicate that inbreeding was an important component of the breeding system in 10 of 14 populations, and were not positively correlated with long-term effective population size.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Little is known of the mating system of H. oldfieldii. In the study of Sampson et al (2015), inbreeding coefficients were positive (F = 0.036-0.198) but did not indicate that inbreeding was an important component of the breeding system in 10 of 14 populations, and were not positively correlated with long-term effective population size.…”
Section: Introductionmentioning
confidence: 76%
“…But these reviews included relatively few studies of species with naturally disjunct population distributions. Several studies of plant species with disjunct distributions have found that genetic diversity is unrelated to census population sizes (Hoebee and Young 2001;Llorens et al 2004;Leimu and Mutikainen 2005;Mathiasen et al 2007;Sampson et al 2015). Indeed, it has been suggested (Holmes et al 2009;Hopper 2009) that naturally disjunct species may have ecological and genetic features that counter the negative effects of small size and isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have similarly emphasized the persistence of prefragmentation patterns (Aguilar et al, 2008;Honnay, Adriaens, Coart, Jacquemyn, & Rold an-Ruiz, 2007;Menges, Dolan, Pickert, Yahr, & Gordon, 2010;Sampson et al, 2015). For example, the influence of historical landscape connectivity on gene flow accounted for the genetic similarity of currently fragmented populations of Globularia bisnagarica in Belgium , while long-term low effective population sizes arising from natural population fluctuations, rather than recent habitat fragmentation, explained low diversity within some populations of Hakea oldfieldii (also Proteaceae from an OCBIL; Sampson et al, 2015). These findings highlight the substantial role that fundamental aspects of biology, ecology and evolution can have in determining population genetic characteristics (Cole, 2003;Duminil et al, 2009;Hamrick & Godt, 1996) and demonstrate that these must be fully considered when interpreting the results of investigations into the effects of relatively recent habitat fragmentation.…”
Section: River Populations Each Formed Separate Clusters and The O'haresmentioning
confidence: 87%
“…The level of fine-scale structure was higher for G. longifolia (b AE SE = À0.063 AE 0.008; S p = 0.066) than G. caleyi (b AE SE = À0.036 AE 0.008; S p = 0.039). Other studies have similarly emphasized the persistence of prefragmentation patterns (Aguilar et al, 2008;Honnay, Adriaens, Coart, Jacquemyn, & Rold an-Ruiz, 2007;Menges, Dolan, Pickert, Yahr, & Gordon, 2010;Sampson et al, 2015). For example, the influence of historical landscape connectivity on gene flow accounted for the genetic similarity of currently fragmented populations of Globularia bisnagarica in Belgium , while long-term low effective population sizes arising from natural population fluctuations, rather than recent habitat fragmentation, explained low diversity within some populations of Hakea oldfieldii (also Proteaceae from an OCBIL; Sampson et al, 2015).…”
Section: River Populations Each Formed Separate Clusters and The O'haresmentioning
confidence: 97%